المحدثون الإندونيسيون بمكة المكرمة في القرن الثالث عشر والقرن الرابع عشر الهجريين سيرهم الذاتية وجهودهم العلمية: The Indonesian Hadith Scholars in Mecca during the 13th and 14th Centuries AH: Their Biographies and Scholarly Contributions - Maulana, Maulana (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2025)
This study explores the biographies of a number of Indonesian hadith scholars who settled in Makkah al-Mukarramah and made notable scholarly contributions there. They actively participated in the hadith scholarly movement in Hijaz during the 13th and 14th centuries AH (19th and 20th centuries CE). The research highlights their biographies, educational backgrounds, teachers, students, and written works, along with their roles in spreading the knowledge of hadith, both in transmission and understanding. The key findings of the study are: 1)- The number of Indonesian hadith scholars who contributed to the dissemination of hadith knowledge in Makkah during the 13th and 14th centuries AH is twelve (12) scholars. 2)- Their efforts in promoting hadith knowledge varied across multiple areas, including teaching in its different forms, authoring scholarly works, and establishing major libraries that housed numerous books and hadith manuscripts. 3)- Among the primary reasons for their excellence in academic achievement in general—and in hadith studies in particular—after the grace of Allah, were: seeking knowledge from an early age, dedicating themselves entirely to study, memorizing hadith texts, and consistently attending the gatherings and lessons of senior scholars.